Evaluation of Habenaria aitchisonii Reichb. for antioxidant, anti-inflammatory, and antinociceptive effects with in vivo and in silico approaches - Asiri, Saeed Ahmed; Shabnam, Madeeha; Zafar, Rehman; Alshehri, Osama M.; Alshehri, Mohammed Ali; Sadiq, Abdul; Mahnashi, Mater H.; Jan, Muhammad Saeed (Frontiers in Chemistry, 2024)
Habenaria aitchisonii Reichb was analyzed in this research, including its chemical composition and its in vitro antioxidant, anti-inflammatory, acute oral toxicity, and antinociceptive activity. The chloroform and ethyl acetate fractions were found to be the most powerful based on in vitro antioxidant, anti-inflammatory, and analgesic assays. The acute oral toxicity of the crude methanolic extract was determined before in vivo studies. The acetic acid and formalin tests were used to measure the antinociceptive effect, and the potential mechanisms involved in antinociception were explored. The carrageenan-induced paw edema test was used to examine the immediate anti-inflammatory effect, and many phlogistic agents were used to determine the specific mechanism. Furthermore, for ex vivo activities, the mice were sacrificed, the forebrain was isolated, and the antioxidant levels of glutathione (GSH), superoxide dismutase (SOD), thiobarbituric acid reactive substances (TBARS) and catalase (CAT) were estimated using a UV spectrophotometer. No toxicity was seen at oral dosages up to 3,000 mg/kg. The antinociceptive impact was much higher than the standard drug. Both the inflammatory and neurogenic phases of the formalin experiment revealed an analgesic effect in the chloroform and ethyl acetate fractions. In carrageenan anti-inflammatory assays, the chloroform fraction (Ha.Chf) was the most potent fraction. We further studied the GC-MS of crude plant extract and found a total of 18 compounds. In the anti-inflammatory mechanism, it was observed that the Ha.Chf inhibits the COX-2 as well as 5-LOX pathways. The results exhibited that this species is a good source of phytocomponents like germacrone, which can be employed as a sustainable and natural therapeutic agent, supporting its traditional use in folk medicine for inflammatory conditions and pain.